2016
DOI: 10.1002/hbm.23239
|View full text |Cite
|
Sign up to set email alerts
|

The role of cortical beta oscillations in time estimation

Abstract: Estimation of time is central to perception, action, and cognition. Human functional magnetic resonance imaging (fMRI) and positron emission topography (PET) have revealed a positive correlation between the estimation of multi-second temporal durations and neuronal activity in a circuit of sensory and motor areas, prefrontal and temporal cortices, basal ganglia, and cerebellum. The systems-level mechanisms coordinating the collective neuronal activity in these areas have remained poorly understood. Synchronize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
64
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(79 citation statements)
references
References 115 publications
14
64
0
Order By: Relevance
“…Interestingly, the particular involvement of beta oscillations is consistent with the association of beta amplitude to temporal judgments in other timing paradigms (e.g. Kononowicz & van Rijn, 2015;Kulashekhar et al, 2016). The exact role of beta oscillations in timing tasks is not yet clear although it has been suggested they might underlie the accumulation of duration evidence (Kulashekhar et al, 2016) or that they relate to starting parameters for decision processes (Kononowicz & van Rijn, 2015).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Interestingly, the particular involvement of beta oscillations is consistent with the association of beta amplitude to temporal judgments in other timing paradigms (e.g. Kononowicz & van Rijn, 2015;Kulashekhar et al, 2016). The exact role of beta oscillations in timing tasks is not yet clear although it has been suggested they might underlie the accumulation of duration evidence (Kulashekhar et al, 2016) or that they relate to starting parameters for decision processes (Kononowicz & van Rijn, 2015).…”
Section: Discussionsupporting
confidence: 71%
“…Kononowicz & van Rijn, 2015;Kulashekhar et al, 2016). The exact role of beta oscillations in timing tasks is not yet clear although it has been suggested they might underlie the accumulation of duration evidence (Kulashekhar et al, 2016) or that they relate to starting parameters for decision processes (Kononowicz & van Rijn, 2015). Although our results did not show an effect of beta-or alpha-band amplitude, the results still implicate pre-stimulus oscillatory activity in timing tasks and give support to the proposed notion that early brain states play a role in the trajectory of temporal decisions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present data, however, do not exclude a possibility that oscillatory signals other than alpha band are involved in time perception. It has been shown that neural oscillations of various frequencies, such as delta (Arnal, Doelling, & Poeppel, ; Cravo, Rohenkohl, Wyart, & Nobre, ), beta (Bartolo & Merchant, ; Fujioka et al, ; Kononowicz & van Rijn, ; Kulashekhar et al, ), and gamma bands (Bartolo, Prado, & Merchant, ; Sperduti, Tallon‐Baudry, Hugueville, & Pouthas, ), contribute to accurate estimation and prediction of time. A recent view, therefore, is that a dominant frequency for timing behaviors is context‐dependent (Wiener & Kanai, ); the brain recruits different frequencies of oscillation signals based on the temporal features of the task being performed.…”
Section: Discussionmentioning
confidence: 99%
“…Based on those behavioral data, here we investigate neural mechanisms of this simplest type of time distortion induced by action preparation (Hagura et al, 2012;Iwasaki et al, 2017). A whole-brain imaging with magnetoencephalography (MEG) would allow us to record neural responses related to time perception, such as a slow build-up (climbing) activity in the medial frontal region (Elbert, Ulrich, Rockstroh, & Lutzenberger, 1991;Macar, Vidal, & Casini, 1999;Merchant, Zarco, Perez, Prado, & Bartolo, 2011;Parker, Chen, Kingyon, Cavanagh, & Narayanan, 2014;Pfeuty, Ragot, & Pouthas, 2003;Wittmann, 2013) and neural oscillations at various frequencies (Bartolo & Merchant, 2015;Fujioka, Ross, & Trainor, 2015;Kulashekhar, Pekkola, Palva, & Palva, 2016;Wiener & Kanai, 2016). Our previous results (Iwasaki et al, 2017) predict some sort of visual-motor interaction occurring in the time-processing regions in the brain (Harrington, Haaland, & Knight, 1998;Ivry & Spencer, 2004;Lewis & Miall, 2003;Merchant, Harrington, & Meck, 2013).…”
Section: Introductionmentioning
confidence: 99%